Allopregnanolone as a Regenerative Therapeutic for Alzheimer's Disease: Phase 2 proof‐of‐concept clinical trial using hippocampal volume as a surrogate endpoint. (20th December 2022) - Hernandez, Gerson D; Lopez, Claudia M; Raikes, Adam C.; Rodgers, Kathleen E.; Matthews, Dawn C; Cutter, Gary R; Schneider, Lon S.; Brinton, Roberta Diaz
Abstract: Background: Given that hippocampal volume is a well‐established imaging biomarker predictive of cognitive decline although not itself a measure of cognition, we propose its use as a surrogate endpoint to test the efficacy of allopregnanolone as a regenerative therapeutic for mild AD. Method: Phase 2 multi‐center, double‐blind, parallel‐group, randomized‐controlled clinical trial. A total of 20 sites will recruit 200 participants with mild AD, 100 participants per treatment arm. Eligible participants are male or female, age 55 to 80 years old, diagnosed with probable AD, with a MMSE between 20‐26 and APOE ε4 genotype (3/4 and 4/4). Participants will be randomized to 4 mg Allo (administered intravenously over 30 minutes, once per week) or matching placebo, 1:1 allocation, for a 12‐month period. After 12 months, all participants in the placebo group will be crossed‐over to receive Allo for the remainder of the study (6 month open‐label phase). Brain imaging to evaluate the primary endpoint will be conducted at baseline, 6 and 12 months. A critical component of this trial is that all imaging sites participating in the trial are capable of performing both basic and advanced MRI sequences required in the protocol. Result: Primary Endpoint is Mean rate of change in hippocampal volume at 12 months. Secondary Endpoints include mean rate of change in cognitive outcomes (CANTAB‐PAL, ADAS‐Cog11), functional outcomes (ADCS‐iADL) and safety outcomes at 12 months. Exploratory endpoints include other imaging outcomes (regional brain volumes, white matter fiber tract diffusion measures as determined by DTI, average intrinsic connectivity as determined by resting state fMRI, and cerebral region cerebral blood flow); blood‐based biomarkers of target engagement; other cognitive and functional outcomes (CDR‐SB score, ADAS‐Cog14 score, MMSE score, NPI‐Q score, EuroQol 5‐Dimension / 5‐Level (EQ‐5D‐5L) health‐related quality of life scale scores, QoL‐AD score, Zarit Burden Interview Questionnaire score at 12 and 18 months. Additionally, change from baseline to 6, 12 and 18 months in open‐label treatment participants switching from placebo to Allo at 12 months in the above endpoints. Conclusion: Results from this study will validate previous findings indicating that allopregnanolone may exert both regenerative and neuroprotective effects on structure and connectivity in the Alzheimer's brain.